In vitro Effects of Punica granatum Ellagitannins on Adult Worms of Schistosoma mansoni - Abozeid KH; El-Badawy MF; Mahmoud S; Shohayeb MM (Dove Medical Press, 2020)
Khalid H Abozeid, 1 Mohamed F El-Badawy, 2, 3 Soheir Mahmoud, 4 Mohamed M Shohayeb 5 1Department of Microbiology, College of Medicine, Taif University, Taif, Kingdom of Saudi Arabia; 2Department of Microbiology and Immunology, Faculty of Pharmacy, University of Sadat City, Sadat City, Menoufia Governorate, Egypt; 3Division of Pharmaceutical Microbiology, Department of Pharmaceutics and Industrial Pharmacy, College of Pharmacy, Taif University, Taif, Kingdom of Saudi Arabia; 4Parasitology Department, Theodor Bilharz Research Institute, Imbaba, Giza, Egypt; 5Department of Microbiology and Biotechnology, Faculty of Pharmacy, Delta University for Science and Technology, Gamasa, EgyptCorrespondence: Khalid H Abozeid; Mohamed F El-Badawy Email Khaled_abozeid@hotmail.com; m.elbadawy@tu.edu.saAbstract: Schistosomiasis ranks second behind malaria in terms of overall morbidity and mortality. We evaluated the lethal effect of Punica granatum ellagitannins, extracted from the fruit rind, placenta and barks of the root and stem, on adult worms of Schistosoma mansoni (S. mansoni). All four ellagitannins were lethal to S. mansoni adult worms. However, while the rind ellagitannins were the most potent, placental ellagitannins were the least. Rind ellagitannins were capable of killing 40% of adult worms at a concentration of 25μg/mL after 5 days. The killing of 100% of the worms was achievable by rind ellagitannins at a concentration of 50μg/mL after 5 days. The LD 50S of the rind ellagitannins after 96h and 120h were 41.25 μg/mL and 28.73 respectively. Ellagitannins-treated worms suffered from erosions, wrinkles, swellings and losses, degenerations of the surface tubercles and tegument. In addition, ellagitannins induced deformation and degradation of oral and ventral suckers and degenerations in the muscles of worms. Ellagitannins also caused a separation of coupled worms and reduction of their motility. Data obtained suggest that ellagitannins of pomegranate could be considered as a cheap candidate for the treatment of ...